2016
DOI: 10.1159/000443932
|View full text |Cite
|
Sign up to set email alerts
|

Chitotriosidase: A New Inflammatory Marker in Diabetic Complications

Abstract: Chitotriosidase (CHIT1) belongs to chitinase family. So far this enzyme has been the best investigated human chitinase regarding its biological activity and association with various disorders. In a healthy population, CHIT1 activity is very low and originates in the circulating polymorphonuclear cells. Conversely, during the development of acute/chronic inflammatory disorders, the enzymatic activity of CHIT1 increases significantly. Recently, CHIT1 has also been involved in the pathogenesis of diabetes mellitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 60 publications
1
16
1
Order By: Relevance
“…Lipid accumulation promotes gene expression in macrophages, affecting the inflammatory process that occurs in atherogenesis [33] . Higher concentrations of chitotriosidase have been reported in the serum of patients with atherosclerosis than in controls (55-fold increase) as well as in sarcoidosis patients [29][30][31][32] . Chitinase 1 plays a role as inflammatory and profibrotic molecule in both diseases, suggesting that it may be a useful disease biomarker and indicator of atherosclerotic plaque formation, as well as in pulmonary granulomatous inflammation [34][35][36] .…”
Section: Chitotriosidase In Atherosclerosis and Sarcoidosismentioning
confidence: 97%
See 1 more Smart Citation
“…Lipid accumulation promotes gene expression in macrophages, affecting the inflammatory process that occurs in atherogenesis [33] . Higher concentrations of chitotriosidase have been reported in the serum of patients with atherosclerosis than in controls (55-fold increase) as well as in sarcoidosis patients [29][30][31][32] . Chitinase 1 plays a role as inflammatory and profibrotic molecule in both diseases, suggesting that it may be a useful disease biomarker and indicator of atherosclerotic plaque formation, as well as in pulmonary granulomatous inflammation [34][35][36] .…”
Section: Chitotriosidase In Atherosclerosis and Sarcoidosismentioning
confidence: 97%
“…Atherosclerosis is associated with accumulation of lipids in artery walls after deposition of LDL cholesterol and fibrous matrix. In the early stage of this disease, monocytes differentiate into foam cells (lipidloaded macrophages generated by massive uptake of modified LDL) that take part in inflammatory responses and tissue remodeling in the arterial intima (vessel lumen narrowing and intimal thickening associated with increased risk of thrombosis) [29][30][31][32] . Lipid accumulation promotes gene expression in macrophages, affecting the inflammatory process that occurs in atherogenesis [33] .…”
Section: Chitotriosidase In Atherosclerosis and Sarcoidosismentioning
confidence: 99%
“…It has been shown that CHIT1 levels increased significantly during the process of macrophage maturation towards the phenotypes of M1/M2 macrophages. While stimulation by TLR ligand/ IFN-γ leads to classical M1 activation, stimulation by IL-4/IL-1 leads to M2 activation [22]. It has been reported that IL-4 treatment induced the expression of mRNA CHIT1 and activated PPAR-γ [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Recent in-vivo and in-vitro studies suggest that ChT is involved at multiple points in different inflammatory and infectious diseases [10,[17][18][19][20][21] although the molecular mechanism of the ChT is far from being completely resolved in these conditions [10,22]. It was reported increased plasma ChT activity in neonates with fungal infection [10].…”
Section: Discussionmentioning
confidence: 99%